Equations » Fractional equations

To solve a fractional equation you have to remove the fraction by multiplying both sides of the equation with the denominator(s).
Important: Check your solutions. Perhaps a solution will not have an outcome in the original equation. See example 4.

Example 1 with the card method
1202x – 9 = 24
 Gebogen pijl naar beneden card method: card on 2x – 9
2x – 9 = 5
2x = 14
x = 7

Example 1 with multiplying by the denominator
1202x – 9 = 24
 Gebogen pijl naar beneden both sides times (2x – 9)
120 = 24(2x – 9)
120 = 48x – 216
336 = 48x
x = 7

Example 2
3 – 5xx + 3 = –2
 Gebogen pijl naar beneden both sides times (x + 3)
3 – 5x = –2(x + 3)
3 – 5x = –2x – 6
3 – 5x = –6
–3x = –9
x = 3

Example 3
x + 13x – 2 = x – 3
 Gebogen pijl naar beneden both sides times (x – 2)
x + 13 = (x – 3)(x – 2)
 x + 13 = x2 – 5x + 6
x2 + 6x + 7 = 0 
x2 – 6x – 7 = 0 
(x + 1)(x – 7) = 0
x = –1 or x = 7

Example 4
12x + 3 3x2x + 6 
 Gebogen pijl naar beneden cross products
12(2x+ 6) = 3x(x + 3)
 24x + 72 = 3x2 + 9x
–3x2 + 15x + 72 = 0 
x2 – 5x – 24 = 0 
(x – 8)(x + 3) = 0 
x = 8 of x = –3

When we fill in x = –3 into the original equation we will get no outcome because you will get a division by zero. Therefore only x = 8 is the solution.

Example 5
6x2 – 12x2 – 12 = 0
 Gebogen pijl naar beneden card method: de numerator must be 0!
6x2 – 12 = 0 
6x2 = 12 
x2 = 2 
x = square root(2) or x = –square root(2)

Example 6
xx – 1 + 2x + 1 = 2
 Gebogen pijl naar beneden both sides times (x – 1)

 Gebogen pijl naar beneden both sides times (x + 1)
x2(x – 1)x + 1 = 2(x – 1)
x(x + 1) + 2(x – 1) = 2(x – 1)(x + 1)
x2 + x + 2x – 2 = 2(x2 – 1)
x2 + 3x – 2 = 2x2 – 2
x2 + 3x = 0 
x(x – 3) = 0
x = 0 or x = 3

Example 7
x2 – 16x2 + 3x – 4 = x20
(x + 4)(x – 4)(x + 4)(x – 1) = x20
x – 4x – 1 = x20
 Gebogen pijl naar beneden cross products
x(x – 1) = 20(x – 4)
x2 – x = 20x – 80 
x2 – 21x + 80 = 0 
(x – 5)(x – 16) = 0
x = 5 or x = 16